2007
DOI: 10.1063/1.2747680
|View full text |Cite
|
Sign up to set email alerts
|

Mixing enhancement in coaxial jets through inflow forcing: A numerical study

Abstract: Direct numerical simulations are performed to analyze the flow dynamics and the mixing properties of natural ͑unforced͒ and excited coaxial jets at moderate Reynolds number. First, the study of the natural coaxial jet, with species injected in the outer jet alone, allows us to understand the role of the coherent vortices on the mixing process during the transition stage. It is observed that the global flow behavior is controlled by the dynamics of the outer shear layer during the transition. The streamwise vor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 54 publications
(80 reference statements)
2
18
0
Order By: Relevance
“…A constant uniform velocity U o was imposed as inflow condition. Unlike the case of [10] or spatially developing turbulent shear layers [1] where the design of proper realistic turbulent inflow conditions is an issue, no superimposed noise was necessary in the present case. The main reason is that for the considered Reynolds number regime Re = 500-2,000, the boundary layer around the cylinder is laminar above the flow separation and gets turbulent in the separated shear layer downstream in the near-wake [32].…”
Section: Numerical Toolsmentioning
confidence: 74%
“…A constant uniform velocity U o was imposed as inflow condition. Unlike the case of [10] or spatially developing turbulent shear layers [1] where the design of proper realistic turbulent inflow conditions is an issue, no superimposed noise was necessary in the present case. The main reason is that for the considered Reynolds number regime Re = 500-2,000, the boundary layer around the cylinder is laminar above the flow separation and gets turbulent in the separated shear layer downstream in the near-wake [32].…”
Section: Numerical Toolsmentioning
confidence: 74%
“…This seminal work initiated many experimental studies which revealed the large potential of active control techniques. [15][16][17][18][19][20][21][22][23] In this paper, we combine passive and active flow control techniques to rectangular turbulent jets, and analyse the resulting flow field. The former is obtained by using a rectangular shape with various aspect ratios of the jet and the latter is obtained by imposing at the jet inlet an excitation with a specific amplitude and frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Stanley et al [13], Reichert and Biringen [14] did DNS of a compressible plane jet exhausting into a parallel stream. Balarac et al [15,16] performed DNS of coaxial jet at moderate Reynolds with high velocity ratio.…”
mentioning
confidence: 98%